The archaeology of forest exploitation and change in the tropics during the Pleistocene: The case of Northern Sahul (Pleistocene New Guinea). (20th August 2017) - Summerhayes, Glenn R.; Field, Judith H.; Shaw, Ben; Gaffney, Dylan
Abstract: The first human arrivals in northern Sahul (New Guinea) encountered new environments, flora and fauna, yet they appear to have rapidly adapted to the challenges of settlement in these different ecological niches. Our paper looks at these adaptations and makes a contribution in understanding the temporal and geographical diversity of rainforest environments occupied by our species. Most of our understanding of these events comes from palaeo-environmental and archaeological records. Here we review the current evidence for the impact of people in forested environments with a view to model landscape management practices from the earliest arrivals at c.50, 000 years ago through to the Early Holocene. The first Sahul colonisers were remarkably dynamic, attested to by their rapid dispersal across Sahul in a relatively short time span, and not all would necessarily have arrived in Sahul by the most northern pathway discussed here. The model presented here provides a heuristic framework within which new data can be tested to further our understanding of human activities and subsistence strategies across a diverse range of New Guinea landscapes.